(untitled) - Schneider, Stephen E. (Boston, 2007)
Pathways to Astronomy is designed more like a series of mini-lectures instead of a monograph of the entire field of astronomy. The same material covered in other introductory astronomy texts is included, but this is broken up into smaller self-contained units. These units are woven together to flow naturally for the person who wants to read the text like a book, but it is also possible to assign them in different orders, or skip certain units altogether. Professors can customize the units to fit their course needs. They can select individual units for exploration in lecture while assigning easier units for self-study, or they can cover all the units in full depth in a content-rich course. With the short length of units, students can easily digest the material covered in an individual unit before moving onto the next unit.
Keywords: Astronomy,Thiên văn học